INTEGRASI MAQASHID SYARIAH DALAM PRAKTIK MANAJEMEN SUMBER DAYA INSANI : STUDI KASUS PADA BMT MUAMALAH MANDIRI PACITAN - Hartini, Sri; Anantyasari, Malta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the integration of Maqashid Sharia (Islamic Principles) into Human Resource Management (MSDI) practices at BMT Muamalah Mandiri. The study employed a qualitative approach with a case study design to deeply understand the dynamics of maqashid value implementation within MSDI functions. Data were obtained through in-depth interviews, observation, and documentation, then analyzed using the Miles and Huberman interactive model through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that maqashid values ​​have been internalized in MSDI practices, particularly in recruitment, training and development, performance appraisal, and work environment management. The hifz al-din dimension is reflected in religiosity- and moral-based recruitment, hifz al-aql in spiritual and competency development, hifz al-mal in trustworthiness- and integrity-based assessment, and hifz al-nafs in efforts to create a conducive work environment. However, this implementation remains substantive and has not been systematically institutionalized in the form of SOPs, performance indicators, or formal maqashid-based policies. This study finds that the primary challenge in integrating maqashid (Islamic principles) into Islamic microfinance institutions (MSDI) lies not in internalizing values, but in transforming them into a measurable managerial system. Therefore, this study proposes a conceptual model for maqashid-based MSDI that emphasizes the balance between internalizing spiritual values ​​and strengthening organizational systems. This research contributes to the development of Islamic MSDI studies, particularly at the level of Islamic microfinance institutions.